2021
DOI: 10.11646/zootaxa.4970.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Neotropical crickets: New species and notes on the classification of Field Crickets genera Anurogryllus and Gryllus (Orthoptera: Gryllidae: Gryllinae)

Abstract: In this contribution to the American Field and Short-tail crickets, two new species from the continental and insular area of Colombia are described. Anurogryllus (Urogryllus) edithsantosum n. sp. from the Meta department, is more related to some Caribbean species, and its genital structure fits the morphological current definition of the subgenus Urogryllus, although it has pseudepiphallic median lophi covered with hairs, as it happens in the species of the subgenus Pilosogryllus. The same way, Gryllus (Gryllu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 731 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…With the daily acoustic activity pattern for each sonotype, we were able to sample the prioritized species and match four out of seven species. Despite recent improvement in taxonomic work in the group for Colombia ( Cadena-Castañeda et al, 2020 , 2021 ), and impressive research on sound production and reception ( Baker et al, 2019 ; Celiker, Jonsson & Montealegre-Z, 2020 ), we found taxonomic novelties from this community (O. Cadena-Castañeda, D.A. Gòmez-Morales, O. Acevedo-Charry, J.L.…”
Section: Discussionmentioning
confidence: 76%
“…With the daily acoustic activity pattern for each sonotype, we were able to sample the prioritized species and match four out of seven species. Despite recent improvement in taxonomic work in the group for Colombia ( Cadena-Castañeda et al, 2020 , 2021 ), and impressive research on sound production and reception ( Baker et al, 2019 ; Celiker, Jonsson & Montealegre-Z, 2020 ), we found taxonomic novelties from this community (O. Cadena-Castañeda, D.A. Gòmez-Morales, O. Acevedo-Charry, J.L.…”
Section: Discussionmentioning
confidence: 76%